2000
DOI: 10.1007/s004250000329
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cell death induces temperature-sensitive lethality in hybrid seedlings and calli derived from the cross of Nicotiana suaveolens × N. tabacum

Abstract: Hybrid lethality expressed in the interspecific hybrid of Nicotiana suaveolens Lehm. x N. tabacum L. cv. Hicks-2 is one of the mechanisms for reproductive isolation and it is temperature-sensitive. Apoptotic changes were detected in the cells of hybrid seedlings and calli expressing lethality at 28 degrees C but not under high-temperature conditions (36 degrees C), when the lethality is suppressed. Condensation of chromatin, fragmentation of nuclei and cytoplasmic reduction are the cytological changes associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
1
35
1
Order By: Relevance
“…Seedlings from N. suaveolens×N. tabacum develop browning at the hypocotyl and die at the cotyledonary stage via apoptotic cell death (Yamada et al 2000). The same lethal symptoms are observed in hybrids derived from the reciprocal cross through test-tube pollination and ovule culture (Tezuka and Marubashi 2004).…”
mentioning
confidence: 79%
“…Seedlings from N. suaveolens×N. tabacum develop browning at the hypocotyl and die at the cotyledonary stage via apoptotic cell death (Yamada et al 2000). The same lethal symptoms are observed in hybrids derived from the reciprocal cross through test-tube pollination and ovule culture (Tezuka and Marubashi 2004).…”
mentioning
confidence: 79%
“…Q chromosome may carry a gene or genes that induced lethal hybrid seedlings from a cross between N. tabacum and N. suaveolens. Yamada et al (2000) have recently showed that the cell death of hybrid seedlings between N. suaveolens and N. tabacum was due to apoptosis. A gene or genes on the Q chromosome might be related to the process of apoptotic cell death in this cross.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that hybrid lethality in the genus Nicotiana showed characteristic features of apoptosis (Marubashi et al 1999, Yamada et al 2000. The hybrid seedlings between N. suaveolens and N. tabacum showed DNA fragmentation, chromatin condensation and nuclear fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…repanda expressing hybrid lethality. Moreover, Yamada et al (2000) reported that hybrid seedlings and calli derived from the cross N. suaveolensϫN. tabacum showed lethality within 2 weeks after germination at 28°C but not under high temperature conditions (36°C).…”
mentioning
confidence: 99%